Kardiyovasküler Cerrahi ve Koroner Yoğun Bakım Ünitesinden Taburcu Olan Hastaların Yoğun Bakım Deneyimlerinin Belirlenmesi - Çağlayan, Hakan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The aim of this study is to determine the intensive care experience of patients who were discharged from the coronary intensive care and cardiovascular surgery clinic.This research was carried out according to descriptive cross-sectional research design. The population of the study was consist of 114 patients of an university hospital in Turkish Republic of Northern Cyprus who were moved from the cardiovascular surgery and coronary intensive care unit to normal unit and whose samples met the sampling inclusion criteria. Patient descriptive questionnaire and intensive care experience scale were used for data collection. The normal distribution of the data was evaluated by Kolmogorov-Smirnov test and parametric hypothesis tests were performed. In this research, it was determined that 35,09% of the patients were in the age group of 71 years; mean age of the patients was 63,80 ± 12,56; 63,16% of the patients were male; 78,95% of the patients were married; 33,33% of the patients were primary school graduates and 68,42% of the patients were not employed. Additionally, 49,12% of the patients duration of the intensive care the intensive care unit for 2 days, 76,32% of the patients have not been into the intensive care unit before, 77.19% of patients were not given anesthesia and 82,46% of the patients did not support mechanical ventilation support. The mean total score of the intensive care experiences scale was found to be 55.83 ± 8.43. The highest score average was obtained from awareness of surroundings subscales (17,22 ± 4,04).A statistically significant difference was found between the scores of the patients aged 50 years and total of the intensive care evaluation scale and the frightening experiences in intensive care and recalling experiences in intensive care unit, the scores from the subscales of awareness of surroundings according to the given anesthesia of the patients in the intensive care unit,according to the temperature of the intensive care unit, the sub-dimension scores of awareness of surroundings and Frightening experiences(p<0,05). It was found that the intensive care unit awareness, intensive care experience andsatisfaction of the patients were medium. Identifying patient experiences and factors affecting these experiences in intensive care; It will guide the planning of nursing care by providing information to the patient stressors by intensive care nurses and will help to improve the quality of care and positive / positive patient experiences. Keywords: Cardiovascular Surgery Intensive Care, Coronary Intensive Care, Patient Experiences, Nurse

ÖZ: Bu araştırmanın amacı; Kardiyovasküler cerrahi (KVC) ve Koroner yoğun bakım ünitelerinden (KYBÜ) taburcu olan hastaların yoğun bakım deneyimlerini belirlemektir. Araştırma tanımlayıcı kesitsel araştırma tasarımına uygun yürütülmüştür. Araştırmanın evrenini Kuzey Kıbrıs Türk Cumhuriyeti (K.K.T.C.)'ınde üniversite hastanesinin KYB ve KVC yoğun bakım ünitelenden servise taburcu olan hastalar, örneklemini ise örnekleme dâhil edilme kriterlerlerine uyan 114 hasta oluşturmuştur. Araştırmanın verilerinin toplanmasında ''Hasta Tanıtıcı Özellikler Anketi’’ ve “Yoğun Bakım Deneyim Ölçeği (YBDÖ)” kullanılmıştır. Verilerin normal dağılımı Kolmogorov-Smirnov testi ile değerlendirilmiş ve parametrik hipotez testleri uygulanmıştır. Araştırmada hastaların %35,09’unun 71 yaş ve üstü yaş grubunda yer aldığı ve hastaların yaş ortalamasının 63,80±12,56 olduğu, %63,16’sının erkek, %78,95’inin evli olduğu, %33,33’ünün ilkokul mezunu olduğu ve %68,42’sinin çalışmadığı saptanmıştır. Hastaların %64,04’ünün koroner anjiografi nedeniyle yoğun bakımda yattığı saptanmıştır. Hastaların %49,12’sinin yoğun bakımda 2 gün kaldığı, %76,32’sinin daha önce yoğun bakımda kalmadığı, %77,19’unun yoğunda bakımda uyutulmadığı, %82,46’sının mekanik ventilasyon desteği almadığı tespit edilmiştir. Hastaların Yoğun Bakım Değerlendirme Ölçeği toplam puan ortalamasının 55,83±8,43olduğu, en yüksek puan ortalamasının Çevrenin Farkında Olma alt boyutundan aldıkları (17,22±4,04) saptanmıştır. Araştırmada 50 yaş ve altı hastaların Yoğun Bakım Değerlendirme Ölçeği genelinden ve Yoğun Bakımda Yaşanan Kötümser Deneyimler ve Yoğun Bakımda Yaşanan Deneyimlerin Hatırlanması alt boyutlarından aldıkları puanlar arasında, yoğun bakımda uyutulma durumlarına göre çevrenin farkında olma alt boyutundan aldıkları puanlar arasında, yoğun bakım ünitesinin sıcaklığını uygun bulma durumlarına çevrenin farkında olma ve yoğun bakımda yaşanan kötümser deneyimler alt boyut puanları istatistiksel olarak anlamlıdır (p<0,05). Hastaların yoğun bakım farkındalığının, yoğun bakım memnuniyetlerinin orta düzeyde olduğu saptanmıştır. Yoğun bakımda hasta deneyimlerinin ve bu deneyimleri etkileyen faktörlerin belirlenmesi, yoğun bakım hemşireleri tarafından hasta stresörlerinin bilinmesini sağlayarak hemşirelik bakımının planlamasına rehber olacak ve bakım kalitesinin artırılmasına, olumlu/pozitif hasta deneyimlerine ulaşılmasını sağlayacaktır. Anahtar Kelimeler: Kardiyovasküler Cerrahi Yoğun Bakım, Koroner Yoğun Bakım, Hasta Deneyimleri, Hemşire
Hemşirelik Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Hemşirelik Bölümü, 2019. Tez Danışmanı: Yard. Doç. Dr. Gülten Sucu Dağ.
Keywords: Hemşirelik; Kardiyovasküler Cerrahi Yoğun Bakım; Koroner Yoğun Bakım; Hasta Deneyimleri; Hemşire; Cardiovascular Surgery Intensive Care; Coronary Intensive Care; Patient Experiences; Nurse